2017
DOI: 10.1021/acs.jpclett.7b01857
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Structurally Engineered Carrier Dynamics in Hybrid Quasi-Two-Dimensional Perovskite Thin Films toward Controllable Emission

Abstract: Quasi-two-dimensional Ruddlesden-Popper perovskites driving carrier self-separation have rapidly advanced the development of high-performance optoelectronic devices. However, insightful understanding of carrier dynamics in the perovskites is still inadequate. The distribution of multiple perovskite phases, crucial for carrier separation, is controversial. Here we report a systematic study on carrier dynamics of spin-coated (CHCHCHNH)(CHNH)PbI (n = 3 and 5) perovskite thin films. Efficient electrons transfer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
171
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(190 citation statements)
references
References 45 publications
15
171
3
1
Order By: Relevance
“…In addition, several groups have conducted ultrafast spectroscopic studies and found fast charge transfer in these complicated heterostructures. However, while charge transfers of ≈0.5 ps were detected in (C 10 H 7 CH 2 NH 3 ) 2 (FA) n −1 Pb n I 3 n +1 ( n ≥ 2) (Figure e–g) and (C 6 H 5 CH 2 CH 2 NH 3 ) 2 (CH 3 NH 3 ) n −1 Pb n I 3 n +1 ( n = 3 or 5), ≈500 ps processes were detected in (C 6 H 5 CH 2 CH 2 NH 3 ) 2 (CH 3 NH 3 ) n −1 Pb n I 3 n +1 ( n = 4) (Figure h,i) . It should be noted that the films studied in these reports had similar composition and geometry, and even highly similar domain distribution, while the relaxation time constants differed by orders of magnitude.…”
Section: Charge Transfer and Device Designmentioning
confidence: 97%
“…In addition, several groups have conducted ultrafast spectroscopic studies and found fast charge transfer in these complicated heterostructures. However, while charge transfers of ≈0.5 ps were detected in (C 10 H 7 CH 2 NH 3 ) 2 (FA) n −1 Pb n I 3 n +1 ( n ≥ 2) (Figure e–g) and (C 6 H 5 CH 2 CH 2 NH 3 ) 2 (CH 3 NH 3 ) n −1 Pb n I 3 n +1 ( n = 3 or 5), ≈500 ps processes were detected in (C 6 H 5 CH 2 CH 2 NH 3 ) 2 (CH 3 NH 3 ) n −1 Pb n I 3 n +1 ( n = 4) (Figure h,i) . It should be noted that the films studied in these reports had similar composition and geometry, and even highly similar domain distribution, while the relaxation time constants differed by orders of magnitude.…”
Section: Charge Transfer and Device Designmentioning
confidence: 97%
“…The charge carrier dynamics in (PEA) 2 (MA) n −1 Pb n I 3 n +1 perovskite were investigated by Shang et al by combining TAS, low‐temperature PL, and KPFM . This study unraveled that the multiple phases of perovskites were naturally arranged in the increasing order of n (from small to large) along the direction normal to the substrate and that different n perovskites also distribute within the same planes, parallel to the substrate.…”
Section: Photophysics Of 2d/3d Mixed Dimensional Perovskitesmentioning
confidence: 99%
“…Recently, the amplified spontaneous emission (ASE) and lasing behaviors of 2D RPPs have been demonstrated . However, the lasing is mostly obtained from solution‐processed spin‐coated thin films, in which multiple RPP components inevitably form with different bandgaps that drive cascade carrier transfer and may reshape the build‐up of population inversion . Also, the development of continuous‐wave or electrically driven RPP lasers central for practical applications is still challenging.…”
Section: Auger Decay Lifetime (τAuger) At High Excitation Fluence (P mentioning
confidence: 99%
“…The kinetics at the PB peaks are extracted and fitted by a biexponential function (Figure S8, Supporting Information): the fast (<20 ps) and the slow (>90 ps) decay channels may contribute to the thermalization process and radiative transition, respectively. Generally, owing to the absence of intercompositional charge transfer processes, the lifetimes of as‐exfoliated homologous thin flakes are longer than those of the solution‐processed spin‐coated RPP thin films consisting of multiple compounds . Figure f compares the PL spectra of bulk crystals (near Gaussian‐type) and exfoliated microflakes (near Gaussian‐type).…”
Section: Auger Decay Lifetime (τAuger) At High Excitation Fluence (P mentioning
confidence: 99%